2000
DOI: 10.1021/ol005917h
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Acid Catalysts for Use in Two-Step, One-Flask Syntheses of Meso-Substituted Porphyrinic Macrocycles

Abstract: [reaction: see text] Diverse Lewis acids and Bronsted acids were examined in the two-step, one-flask synthesis of meso-tetraphenylporphyrin, N-confused tetraphenylporphyrin, and tetraphenylsapphyrin. The scope of acid catalysis was found to be very broad, with 35 of 45 acids providing TPP in yields ranging from 5% to 58%. NC-TPP was also widely observed in yields of 1-40%, and TPS was infrequently observed in yields of <1%. Additionally, conditions were found for direct preparation of magnesium TPP and copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
54
1
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 21 publications
(15 reference statements)
3
54
1
2
Order By: Relevance
“…One seminal contribution along these lines was made in 1995 when LatosGrazyń ski and co-workers reported that tetraphenylsapphyrin can be obtained in 1.1 % yield by condensing pyrrole and benzaldehyde under appropriate conditions. [70] Subsequent efforts by Lindsey and co-workers to optimize the synthesis of N-confused porphyrin (obtained in remarkable yields up to 40 %), [79] failed to improve the yield of tetraphenylsapphyrin obtained from this reaction (namely, the direct condensation of pyrrole and benzaldehyde). Indeed, the maximum yield obtained by Lindsey and coworkers was 1.2 %.…”
Section: New Advances In the Area Of Sapphyrin Chemistrymentioning
confidence: 99%
“…One seminal contribution along these lines was made in 1995 when LatosGrazyń ski and co-workers reported that tetraphenylsapphyrin can be obtained in 1.1 % yield by condensing pyrrole and benzaldehyde under appropriate conditions. [70] Subsequent efforts by Lindsey and co-workers to optimize the synthesis of N-confused porphyrin (obtained in remarkable yields up to 40 %), [79] failed to improve the yield of tetraphenylsapphyrin obtained from this reaction (namely, the direct condensation of pyrrole and benzaldehyde). Indeed, the maximum yield obtained by Lindsey and coworkers was 1.2 %.…”
Section: New Advances In the Area Of Sapphyrin Chemistrymentioning
confidence: 99%
“…Chemists have developed a few synthetic methods to provide convenient access to synthesize substituent tetraphenylporphyrin complexes [9][10][11]. The prevalent method of synthesis involves a mixed aldehyde condensation with pyrrole via Adler method in refluxing propionic acid [12].…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] Above all, the synthetic methods of TPPH 2 in the single solvent or solvent-free systems have been widely developed in recent years. [33][34][35] However, the present synthesis of TPPH 2 from the direct condensation of benzaldehyde and pyrrole is still inconvenient and the purity of products directly separated from the filtrate remains to be improved. In our previous reports, 36,37 the synthesis of para-substituted tetraphenylporphyrins with the mixed-solvent method was developed on the research basis of Gonsalves.…”
mentioning
confidence: 99%